2014
DOI: 10.1016/j.jsv.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Oblique incidence sound absorption of parallel arrangement of multiple micro-perforated panel absorbers in a periodic pattern

Abstract: The sound absorption performance of a micro-perforated panel (MPP) absorber array at oblique incidence and in diffuse field is investigated both numerically and experimentally. The basic module of the MPP absorber array consists of four parallel-arranged MPP absorbers with different cavity depths, and the whole MPP absorber array is created by arranging the basic modules in a periodically repeating pattern. A three-dimensional finite element model is used to simulate the acoustic properties of the MPP absorber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(17 citation statements)
references
References 19 publications
2
12
0
2
Order By: Relevance
“…where k x,m , k y,n and γ mn are the wavenumbers in the x, y and z directions, respectively. According to reference [32], the scattered sound wave is expressed in terms of modal expansion.…”
Section: Surface Impedance Of Porous Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…where k x,m , k y,n and γ mn are the wavenumbers in the x, y and z directions, respectively. According to reference [32], the scattered sound wave is expressed in terms of modal expansion.…”
Section: Surface Impedance Of Porous Materialsmentioning
confidence: 99%
“…where the summation runs over all the radiating harmonics only, the second term is the specular reflection and the third term is the scattered sound. The averaged diffuse-field sound-absorption coefficient is defined as follows [32,41]:…”
Section: Surface Impedance Of Porous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Eq. 5 can be assumed to be independent (Wang et al, 2014) of the azimuthal angle φ if the lateral size of the supercell is deep-subwavelength. Otherwise, an asymmetric absorption (Lee and Iizuka, 2019;Wang et al, 2019) would be observed because of the geometric asymmetry, when the incident wave is from the same polar angle but different azimuthal angles.…”
Section: Theoretical Model For Supercell With Different Unit Cellsmentioning
confidence: 99%
“…They concluded that strong local resonance occurs due to different reactance matching conditions for the component MPP absorbers and the resonance frequencies shift due to inter-resonator interactions. Moreover, the oblique incidence sound absorption of parallel arrangement of four MPP absorbers in diffuse field was also investigated both numerically and experimentally [11]. Although the parallel MPP absorber array have the potential to improve sound absorption bandwidth due to multi-resonance of component MPPs, the reported perforation aperture is limited to 0.3–0.8 mm, and therefore the cost for the massive processing will be extremely high.…”
Section: Introductionmentioning
confidence: 99%